2021
DOI: 10.3390/ijerph18116100
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Approach to Determining the Contribution of Saharan Dust to Pollution

Abstract: Air quality is one of the hot topics of today, and many people are interested in it due to the harmful effects that environmental pollution has on human health. For this reason, in recent years, measurement systems based on advanced technology have been implemented to integrate national air quality networks. This study aimed to analyze the air quality data of the monitoring network of the regional agency for environmental protection of the Campania region (Italy), integrated with a monitoring station based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…To further increase the spatial resolution of the measured data, real-time on-road monitoring systems have been developed in recent years which provide information on pollutants with a resolution of 1 km 2 [33] [34]. The knowledge of the pollution levels can lead to the analysis of the events that influence this phenomenon [35]. In particular, the Saharan dusts being classified as PM10, are seen by the measurement systems that include them in the measured concentration without splitting the type of particle: urban particulate is made of metals while Saharan dust particle are made of siliceous compounds [36] [37].…”
Section: Introductionmentioning
confidence: 99%
“…To further increase the spatial resolution of the measured data, real-time on-road monitoring systems have been developed in recent years which provide information on pollutants with a resolution of 1 km 2 [33] [34]. The knowledge of the pollution levels can lead to the analysis of the events that influence this phenomenon [35]. In particular, the Saharan dusts being classified as PM10, are seen by the measurement systems that include them in the measured concentration without splitting the type of particle: urban particulate is made of metals while Saharan dust particle are made of siliceous compounds [36] [37].…”
Section: Introductionmentioning
confidence: 99%
“…[21 -25] This can help identify the main pollutants responsible for the degradation of the materials and take effective measures to protect them. Furthermore, it is important to raise awareness among the general public and stakeholders about the importance of preserving our cultural heritage and the role that each one of us can play in achieving this goal [26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Four papers were collected in the second group concerning novel monitoring technologies. Lotrecchiano et al [ 5 ] aimed to analyze the air quality data of the monitoring network of the regional agency for environmental protection of the Campania region (Italy), integrated with an innovative monitoring station based on IoT technology to highlight criticalities in the levels of pollution. In-depth analyses showed that two events related to Saharan dust occurred, which led to an increase in the measured PM10 values.…”
mentioning
confidence: 99%